Comparing public willingness-to-pay for different low-carbon measures: A case study of Shenzhen, China - Haiyan Hao; Jiaying Lin; Shiyong Qiu; Li Liu; Jiahuan Dai (PLoS ONE, 2025)
Cities in China have made progressive strides in developing low-carbon societies and experimenting with various low-carbon measures. The successful implementation of these low-carbon measures and the subsequent maintenance of relevant amenities rely on the support of local residents. However, there is limited understanding of residents' awareness and support for the different types of low-carbon measures, which can involve different trade-offs. This research addressed this research gap by surveying residents’ willingness-to-pay for five representative low-carbon measures implemented in Shenzhen, a pioneering low-carbon city in China. Surveys were collected from 14 distinct residential areas in Shenzhen, and the analysis results revealed that Shenzhen residents were more inclined to pay for low-carbon measures that directly benefit them personally, as opposed to those serving the collective good. This trend was particularly evident among educated elites. Other notable findings include: 1) respondents aware of the different low-carbon measures in effect were more likely to pay for them; 2) male respondents, new Shenzhen residents (relocated within the last 5 years), high-income individuals, and residents in aging residential areas tended to contribute higher amounts towards low-carbon measures; 3) providing detailed information on carbon mitigation effects significantly increased both the likelihood and the amount of respondents' WTP; 4) the adoption of new-energy vehicles (NEVs) is especially controversial between NEV owners and gasoline vehicle owners. These findings hold implications, such as developing targeted policies and educational interventions, to enhance public awareness and support for low-carbon initiatives, thus fostering sustainability in rapidly growing urban centers like Shenzhen.